Tra Vinh University Journal of Science Number 4 (H. Agricultural Publishing, 2023)
Tra Vinh University Journal of Science are grouped into 04 discipline-specific sections, including: Agriculture - Aquaculture ; Culture - Education - Arts ; Economics - Social Sciences ; Technological - Environmental Sciences.
Keywords: Tạp chí